2020
DOI: 10.4193/rhin20.071
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin for chronic eosinophilic rhinosinusitis with nasal polyp: a placebo-controlled trial

Abstract: BACKGROUND: Chronic eosinophilic rhinosinusitis with nasal polyps (CRSwNP eosinophilic) is characterised by the formation of benign and bilateral nasal polyps. We aimed to compare the effectiveness of azithromycin as an immunomodulator with the use of a placebo in patients presenting with CRSwNP concomitant with asthma and aspirin intolerance after 3 months of treatment and at a 1-year follow-up. METHODOLOGY: We performed a randomised, double-blind, placebo-controlled trial. Patients received 500 mg azithromyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Antibiotics such as azithromycin and doxycycline are occasionally used in CRSwNP treatment. [100][101][102][103][104] Because of limited evidence, the use of leukotriene receptor antagonists (eg, montelukast) is not recommended. 2,105 Our search results include studies showing significant improvements in QoL after medical therapy, including consistent short-term efficacy with intranasal corticosteroids (spray, drops, or exhalation delivery systems) 106 and oral corticosteroids (Table EI).…”
Section: Impact Of Treatment On Qol In Crswnpmentioning
confidence: 99%
“…Antibiotics such as azithromycin and doxycycline are occasionally used in CRSwNP treatment. [100][101][102][103][104] Because of limited evidence, the use of leukotriene receptor antagonists (eg, montelukast) is not recommended. 2,105 Our search results include studies showing significant improvements in QoL after medical therapy, including consistent short-term efficacy with intranasal corticosteroids (spray, drops, or exhalation delivery systems) 106 and oral corticosteroids (Table EI).…”
Section: Impact Of Treatment On Qol In Crswnpmentioning
confidence: 99%
“…Both macrolides and doxycycline are presumed to have treatment effects for CRSwNP through anti-inflammatory mechanisms, which is supported by their observed modulation of inflammatory mediators (351,353) . Macrolides, which have been shown to reduce CRSwNP symptoms and reduce nasal polyp size (354,355) , have been shown to impact both eosinophilic and neutrophilic biomarkers. For example, studies have found significantly lower eosinophil cationic protein (ECP) in nasal secretions in those treated with oral clarithromycin daily for 8 to 24 weeks compared with no antibiotics (356,357) .…”
Section: Antibiotics: Macrolides and Doxycyclinementioning
confidence: 99%
“…Aspirin or nonsteroidal anti-inflammatory drug (NSAID)-exacerbated respiratory disease (AERD/NERD) is characterized by asthma, CRSwNP, and aspirin or nonsteroidal anti-inflammatory drug intolerance [90]. In AERD patients with eosinophilic nasal polyps (>40% eosinophils), LDLT azithromycin treatment significantly reduced symptoms (visual analog scale and SNOT-22) and the need for surgery (74% versus 14%) compared to placebo [75]. In addition, another study showed that azithromycin significantly improved disease clearance in AERD patients compared to placebo [73].…”
Section: Type 2 Vs Non-typementioning
confidence: 99%